Stress Levels Among Older Adults Before and After Empowerment-Based Group Activity Therapy (Gardening and Creative Activities) - Agustia Cahyani; Kartinah Kartinah (Sarana Ilmu Indonesia (salnesia), 2026)
Elderly people in social care often experience limited interaction, leading to loneliness, social isolation, and stress, while previous studies generally only tested one type of therapy. This quasi-experimental study aimed to test the effectiveness of a combination of gardening and creative therapy in reducing stress levels in the elderly using a purposive sampling technique. The intervention was conducted over two days in April 2026, with data collected through the GDS-15 questionnaire the day before and after the activity, then analyzed using a paired sample t-test. The results showed a significant effect on reducing stress levels in the elderly after the intervention (significance value .0001 < 0.05), so Ha was accepted. This combination of therapies has been proven to foster a sense of responsibility and happiness that effectively divert feelings of low self-esteem, loneliness, and boredom; therefore, future researchers are expected to combine this action with other, more relevant therapies.